Psychological determinants in the sports selection process for professional football in Algeria from the players’ point of view - Chehat , mourad; Balboul , moussa (sports creativity, 2025)
This study aimed to determine the psychological characteristics of Algerian professional football players in order to select young talents in football because their great importance in the formation of the sports personality of professional players, for professional and elite clubs. We used the descriptive analytical method for its relevance to the subject. The study population included all the 16 clubs of the Algerian Premier League at the national level. The sample also included all the professional players in these clubs, and we chose an intentional sample. When we used a questionnaire according to the "Licart" seven-scale contains the psychological qualities of the aforementioned axis. this tool allows us to categorize different traits and arrange them according to their importance. The results obtained were in identifying and arranging the qualities that must be emphasized in selecting talented players to bring them to the high and professional level in Algerian football significantly (desire to win, determination, desire to play football), and which got the seventh degree of the "Likart" scale